1999
DOI: 10.1177/000841749906600405
|View full text |Cite
|
Sign up to set email alerts
|

Opportunity, Not Prescription: An Exploratory Study of the Experience of Occupational Engagement

Abstract: Occupational therapy practice is based upon the belief that the use of occupation-as-means can promote the health and sense of well-being of individuals with disability. Despite a firm commitment to the construct of occupation by the profession, little empirical evidence has been generated which supports the basic tenets of practice. In the psychosocial literature, no studies could be located which directly investigated the use of occupation-as-means to mental health. An exploratory study was conducted with ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
101
0
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(117 citation statements)
references
References 38 publications
13
101
0
3
Order By: Relevance
“…The time spent in extrinsically motivated but still individually meaningful occupations may theoretically impact the attendee's intrinsic motivation over time (Deci & Ryan, 2008;Kielhofner, 2008). This reasoning is in agreement with qualitative studies, showing that doing triggers more engagement, which then leads to a spin-off effect in terms of further activity (Leufstadius, Eklund, & Erlandsson, 2009;Rebeiro & Cook, 1999) and intrinsic motivation (Mee & Sumsion, 2001). In the present study, setting own individual goals was highlighted as important for OE.…”
supporting
confidence: 92%
“…The time spent in extrinsically motivated but still individually meaningful occupations may theoretically impact the attendee's intrinsic motivation over time (Deci & Ryan, 2008;Kielhofner, 2008). This reasoning is in agreement with qualitative studies, showing that doing triggers more engagement, which then leads to a spin-off effect in terms of further activity (Leufstadius, Eklund, & Erlandsson, 2009;Rebeiro & Cook, 1999) and intrinsic motivation (Mee & Sumsion, 2001). In the present study, setting own individual goals was highlighted as important for OE.…”
supporting
confidence: 92%
“…It should also result in better satisfaction with the day center services and a higher level of engagement, as the intentions with the freedom of choice system in question was to increase the possibilities for matching individuals' preferences with available offers. According to previous research, such a match has been found to be vital for client satisfaction and engagement (Leufstadius, Eklund, & Erlandsson, 2009;Rebeiro & Cook, 1999;Tjörnstrand et al, 2011). Finally, since research has shown that one of the main advantages with attending a day center is an increased number of social contacts (Argentzell et al, 2013) one can also expect a change in that respect.…”
Section: Introductionmentioning
confidence: 95%
“…The meaning of occupational engagement was later explored by Rebeiro and Cook (1999). They presented their findings in terms of a conceptual model named "occupational spin-off" and discuss this in terms of occupation-as-means.…”
Section: Findings From the Literaturementioning
confidence: 99%
“…By coming from the perspective of occupation-as-means, Rebeiro and Cook (1999) acknowledged that occupations do not always contain an element of subjective significance for an individual. Feelings of competence and confidence appear to be described as two features of sustaining occupational engagement (Rebeiro & Cook, 1999).…”
Section: Findings From the Literaturementioning
confidence: 99%
See 1 more Smart Citation